Evaluasi Desain Struktur Kursi Kerja Kayu Menggunakan Simulasi Finite element method (FEM) - Ramadhan Fitrianto, Taufik; Muhammad, Atdfal; Prakoso, Galih (P3M Politeknik Negeri Cilacap, 2026)
Existing office chair designs often inadequately consider user anthropometry and structural strength, which may reduce comfort and compromise user safety. This study aims to redesign an office chair based on employees’ anthropometric data and to validate improvements in its structural performance using the Finite Element Method (FEM). Numerical simulations were conducted in Autodesk Inventor under incremental static loads ranging from 500 to 2000 N applied to the seat, with an additional backrest load equal to 40% of the seat load. The results indicate that the original chair design could withstand a maximum load of approximately 2,038 N, with a maximum deformation of 3.91 mm and a minimum factor of safety of 1.02. In contrast, the redesigned chair sustained loads up to approximately 7,651 N, with a maximum deformation of 4.21 mm and a factor of safety of 3.83. This represents an improvement in load-bearing capacity of about 3.7 times. The enhancement was primarily achieved through structural optimization, including increased wooden cross-sections and fewer joints. The findings demonstrate that integrating ergonomic design with FEM-based structural analysis provides a reliable engineering approach to improve the performance of wooden office chairs prior to fabrication.